Exploratory retrospective study of risk factors for thromboembolism treated with multi-kinase inhibitor pazopanib or lenvatinib. Issue 4 (26th August 2020) - Nio, Kenta; Tsuchihashi, Kenji; Taguchi, Keisuke; Yoshihiro, Tomoyasu; Yamaguchi, Kyoko; Ito, Mamoru; Moriyama, Shohei; Fukata, Mitsuhiro; Fujiwara, Toshifumi; Setsu, Nokitaka; Endo, Makoto; Matsumoto, Yoshihiro; et al.
Abstract : Tyrosine kinase inhibitors (TKI) work against various types of cancer by inhibiting angiogenic signaling. Little is understood about the incidence, characteristics, and risk factors associated with thromboembolism induced by TKI in routine clinical practice. We retrospectively analyzed data derived from 29 patients with thyroid cancer or soft tissue sarcoma (STS) treated with lenvatinib (n=10) and pazopanib (n=19). Eight (arterial n=4; venous n=4) thromboembolic events developed in 6 (20%) patients. Thromboembolisms occurred during a mean of 149 (range, 42–847) days from starting TKI. The primary disease progressed in all patients with thromboembolism. The overall survival durations of patients with and without improved thromboembolism were 572 [95% confidence interval (CI), 225– 918] and 176 (95% CI, 84–394) days, respectively, which did not significantly differ ( P =0.33). Patients with and without improved thromboembolism survived after onset for 122 (95% CI, 71–173) versus 27 (95% CI, 21–42) days ( P =0.049), which significantly differed. Univariate analysis and variate selection for multivariate analysis selected a history of thromboembolism as the most powerful risk factor for new thromboembolism. In summary, the frequency of thromboembolism in clinical practice was higher than that in previous clinical trials. Furthermore, a history of thromboembolism was a risk factor for the development of new thromboembolism in patients treated with TKI. Thromboembolism developed particularly as the primary disease progressed. Our findings require validation in a large-scale study.